ANIKA KAO FATALNA ŽENA – DEMONIZACIJA ŽENSKOSTI U PRIPOVIJETCI ANIKINA VREMENA IVE ANDRIĆA (Philological Studies, 2019)
From the standpoint of a feminist literary critic, the demonization of women in the form of a stereotype/archetype femme fatale is usually interpreted as a patriarchal ideological construction symbolizing male fear of female emancipation, connected with the periods of crisis of the patriarchal societal order. Unlike other feminist critics, in her work Soft Shed Kisses – Re-visioning of Famme Fatale in English Poetry of the 19th Century Malgorzata Luczynska-Holdys claims that the stereotypical character of femme fatale in literature is often used to criticize male point of view. This interpretation is the consequence of male voices in the texts analyzed by Luczynska-Holdys, which ascribe fatality to all women. This interpretation is based on the thesis that in the novel Anika’s Times it is possible to observe the process of demonization of women in the minds of central male characters, as well as in the stories produced by the patriarchal male-centered community. Therefore, the novel does not simply reproduce the patriarchal stereotypical construction of fatal women but it enables a certain level of its reflection and criticism.
Keywords: gender, fame fatale, demonization, castration, cultural crisis, sacrificial revival, (meta)naration